Theodore of Mopsuestia - McLeod, Frederick G. (The early church fathers, 2009)
Part I: Introduction -- Theodore's secondary literature -- Theodore's exegetical method -- Examples of Theodore's exegetical method -- God's indwelling of good pleasure -- Theodore's understanding of hypostasis and prospon -- The functional unity of Christ's natures -- Assessment -- Part II: Texts -- General introduction to the texts -- In opposition to the allegorists -- Commentary on Psalm 8 -- Commentary on the creation of Adam and Ave -- Commentary on John's Gospel -- Commentary on Philippians 2:6-11 -- Selections from the commentaries on Galatians, Ephesians, and Colossians -- On the Incarnation -- In opposition to Apollinaris -- Catechetical homilies -- Conciliar anathemas